2017
DOI: 10.1080/14719037.2017.1285112
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive styles, user acceptance and commitment to strategic plans in public organizations: an empirical analysis

Abstract: Given the lack of insights into the micro-determinants of strategic planning (SP) in public organizations, this study uses information-processing theory and self-efficacy theory to investigate individual-level predictors of commitment to strategic plans among planning team members (PTMs). Specifically, we investigate whether plan commitment is contingent upon the fit between PTMs' preferred way of information-processing (i.e. their cognitive style) and the information-processing characteristics underlying SP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 58 publications
2
62
0
1
Order By: Relevance
“…Indeed, the SP process could adopt all aspects of the Harvard policy model, synoptic planning theory, and goal‐setting theory but not include the required human resources to become comprehensive. Theorizing about SP's impact on OP thus requires an assessment of both the process of SP and the human resources actually involved in SP (George ).…”
Section: Discussion: Implications For Theory Research and Practicementioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, the SP process could adopt all aspects of the Harvard policy model, synoptic planning theory, and goal‐setting theory but not include the required human resources to become comprehensive. Theorizing about SP's impact on OP thus requires an assessment of both the process of SP and the human resources actually involved in SP (George ).…”
Section: Discussion: Implications For Theory Research and Practicementioning
confidence: 99%
“…Much of the SP research has used single cross‐sectional surveys to measure the independent and dependent variables (e.g., Elbanna ; George et al ). However, some studies have included multiple‐source data to measure OP (e.g., Jimenez ; Poister, Pasha, and Edwards ).…”
Section: Moderators In the Strategic Planning–organizational Performamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the interviews suggested that widespread participation (both internally and externally) illustrates that the SP process is broadly supported throughout the organization and not just a top-down process. George et al (2017) focus on 439 planning team members from 203 Flemish municipalities. They identify predictors of planning team members' commitment to implement strategic plans.…”
Section: Resultsmentioning
confidence: 99%